2009
DOI: 10.1111/j.1478-3231.2009.01970.x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni coinfection could have a protective effect against mixed cryoglobulinaemia in hepatitis C patients

Abstract: There is an apparent protective effect of S. mansoni coinfection against mixed cryoglobulinaemia in chronic hepatitis C patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…[25] Considering the subcategory IIc, our study correlated with Abbas, O.M., et al who reported that schistosoma coinfection could have a protective effect against mixed cryoglobulinaemia (CG) [in which renal disease more common than in Type I (CG)] in hepatitis C patients, so less renal impairment. [26] However, in contrary to our study, Kamal, S., et al reported that patients with concomitant HCV and bilharziasis had a marked increase in the Child-Pugh score (more advanced liver disease), more frequent episodes of upper gastrointestinal bleeding, more renal impairment. [24] All these factors not present in our patients (our patients in group II were compensated, no gastrointestinal bleeding, so no renal abnormality found.…”
Section: Discussioncontrasting
confidence: 99%
“…[25] Considering the subcategory IIc, our study correlated with Abbas, O.M., et al who reported that schistosoma coinfection could have a protective effect against mixed cryoglobulinaemia (CG) [in which renal disease more common than in Type I (CG)] in hepatitis C patients, so less renal impairment. [26] However, in contrary to our study, Kamal, S., et al reported that patients with concomitant HCV and bilharziasis had a marked increase in the Child-Pugh score (more advanced liver disease), more frequent episodes of upper gastrointestinal bleeding, more renal impairment. [24] All these factors not present in our patients (our patients in group II were compensated, no gastrointestinal bleeding, so no renal abnormality found.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study detected a lower prevalence of MC among Egyptian patients with cutaneous manifestations of HCV infection (10.169%) than expected. These findings suggest that cryoglobulinaemia in the context of hepatitis C may be less prevalent in Egypt than in other areas and this could be attributed to (1) the apparent protective role of Schistosoma mansoni coinfection, which is common in Egypt, against the development of immune-mediated diseases such as MC in chronic HCV-infected patients [ 26 ]. Helminthic infections are characterized by a strong T helper-2 response as well as an overall downregulated immune system which are both beneficial in protecting the host from developing autoimmune diseases and/or relieving symptoms of an established autoimmune disease [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors had reported that cryoglobulinaemic vasculitis was significantly more common in female population with HCV infection [ 38 ], although this association was nonsignificant in another report [ 39 ]. Abbas et al [ 26 ] reported that cryoglobulinaemia in their Egyptian patients with HCV was not related to age or progression of cirrhosis; meanwhile it was negatively correlated with serum ALT and serum AST levels, and it was positively correlated with female gender. The discrepancy in the results could be due to variation in sample size and inclusion criteria among different studies.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Previously, Various techniques have been used for decellularization that involves any combination of physical, chemical and enzymatic methods with various solvents, detergent, and enzyme to lyse the cells while creating the free volume spaces upon which native host cells can proliferate. 10 SDS is the most used of the chemical agent in the decellularization process because of their capabilities in cells removal by dissolving the cell membranes. However, it also disrupts the integrity structure of ECM that resulted in weak biomechanical properties of tissues.…”
Section: Introductionmentioning
confidence: 99%